2023
DOI: 10.1039/d2ta09632c
|View full text |Cite
|
Sign up to set email alerts
|

A highly permeable porous organic cage composite membrane for gas separation

Abstract: Membrane-based separation processes have become the focus of research in the field of CO2/N2 and CH4/N2 separation due to their green, energy saving and high efficiency characteristics. However, the insufficient...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
(68 reference statements)
0
12
0
Order By: Relevance
“…Fabrication of the PDMS Membrane: The PDMS membrane was fabricated according to the method reported in our previous work. [48] A total of 3.4 g L −1 PDMS, 2.8 g L −1 tetraethoxysilane (TEOS) and 2.8 g L −1 dibutyltin dilaurate (DBD) were mixed in n-heptane to obtain a PDMS solution under continuous stirring for 30 min. After standing for 30 min at 30 °C, the PDMS solution was coated onto the surface of the PSf substrate with a knife gap of 100 μm, followed by drying in an oven at 60 °C for 12 h.…”
Section: Methodsmentioning
confidence: 99%
“…Fabrication of the PDMS Membrane: The PDMS membrane was fabricated according to the method reported in our previous work. [48] A total of 3.4 g L −1 PDMS, 2.8 g L −1 tetraethoxysilane (TEOS) and 2.8 g L −1 dibutyltin dilaurate (DBD) were mixed in n-heptane to obtain a PDMS solution under continuous stirring for 30 min. After standing for 30 min at 30 °C, the PDMS solution was coated onto the surface of the PSf substrate with a knife gap of 100 μm, followed by drying in an oven at 60 °C for 12 h.…”
Section: Methodsmentioning
confidence: 99%
“…193,194 Jiang et al constructed a highly permeable POC composite membrane (TPC-RCC3/mPSf) through crosslinking the classic RCC3 porous organic cage with terephthaloyl chloride (TPC). 182 By calculating the binding energy between the RCC3 cage and gas molecules, it was found that the RCC3 cage exhibits stronger interactions towards CH 4 than N 2 due to its higher polarity and stronger condensation ability.…”
Section: Apm-based Mixed Matrix Membranes (Mmms)mentioning
confidence: 99%
“…a thickness of 252 nm through the interfacial polymerization (IP) reaction [43] , wherein a kind of POC, namely Noria, in an aqueous phase could react with terephthaloyl chloride (TPC) via the formation of C-O bonds under the catalysis of triethylamine [Figure 2A]. Similarly, Jiang et al utilized the IP reaction between the reduced POC (RCC3) and TPC to produce two TPC-RCC3 films (OCF-12 and OCF-13) [44] .…”
Section: Synthesis Through Irreversible Bondsmentioning
confidence: 99%
“…In this context, the dynamic covalent chemistry (DCC), especially the imine condensation, is regarded as the optimal choice for the formation of cage-based COFs, since it allows a self-correction process under thermodynamic control [49] . [43] . Copyright 2020, Elsevier; (B) Schematic illustration of the synthesis of OCF-12 and OCF-13 through the IP reaction [44] .…”
Section: Synthesis Through Dynamic Bondsmentioning
confidence: 99%